2016
DOI: 10.1038/cddis.2016.245
|View full text |Cite
|
Sign up to set email alerts
|

NEMO regulates a cell death switch in TNF signaling by inhibiting recruitment of RIPK3 to the cell death-inducing complex II

Abstract: Incontinentia Pigmenti (IP) is a rare X-linked disease characterized by early male lethality and multiple abnormalities in heterozygous females. IP is caused by NF-κB essential modulator (NEMO) mutations. The current mechanistic model suggests that NEMO functions as a crucial component mediating the recruitment of the IκB-kinase (IKK) complex to tumor necrosis factor receptor 1 (TNF-R1), thus allowing activation of the pro-survival NF-κB response. However, recent studies have suggested that gene activation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…177 SHARPIN was demonstrated to be part of the linear ubiquitination complex (LUBAC), which connects linear ub-linkages to RIPK1 and NEMO (which requires RIPK1 ubiquitination to initiate NF-κB signaling). 162 In line with this idea, chronic inflammation of the skin is triggered upon keratinocyte-specific deletion of FADD, a phenomenon that depends on RIPK3-dependent necroptosis and partially on TNFR1 and CYLD (an enzyme deubiquitinating RIPK1). 162 In line with this idea, chronic inflammation of the skin is triggered upon keratinocyte-specific deletion of FADD, a phenomenon that depends on RIPK3-dependent necroptosis and partially on TNFR1 and CYLD (an enzyme deubiquitinating RIPK1).…”
Section: Necroptosis In the Skinmentioning
confidence: 92%
See 3 more Smart Citations
“…177 SHARPIN was demonstrated to be part of the linear ubiquitination complex (LUBAC), which connects linear ub-linkages to RIPK1 and NEMO (which requires RIPK1 ubiquitination to initiate NF-κB signaling). 162 In line with this idea, chronic inflammation of the skin is triggered upon keratinocyte-specific deletion of FADD, a phenomenon that depends on RIPK3-dependent necroptosis and partially on TNFR1 and CYLD (an enzyme deubiquitinating RIPK1). 162 In line with this idea, chronic inflammation of the skin is triggered upon keratinocyte-specific deletion of FADD, a phenomenon that depends on RIPK3-dependent necroptosis and partially on TNFR1 and CYLD (an enzyme deubiquitinating RIPK1).…”
Section: Necroptosis In the Skinmentioning
confidence: 92%
“…178,179 Therefore, in the absence of SHARPIN, NF-κB signaling is inhibited 180 and aberrant induction of cell death can emerge. 162 In line with this idea, chronic inflammation of the skin is triggered upon keratinocyte-specific deletion of FADD, a phenomenon that depends on RIPK3-dependent necroptosis and partially on TNFR1 and CYLD (an enzyme deubiquitinating RIPK1). 181 Additionally, conditional loss of caspase-8 within the skin leads to a similar inflammatory phenotype, 182 and RIPK3-deficiency is protective for FADD and caspase-8 deficiency in the skin.…”
Section: Necroptosis In the Skinmentioning
confidence: 92%
See 2 more Smart Citations
“…Although previous studies demonstrated that NEMO induces necroptosis by promoting RIPK1/RIPK3 necrosome 139,140 , further studies are needed to better understand the IKK/NF-κΒ-independent role of NEMO in controlling PCD in the liver. Nevertheless, based on these studies, the use of small molecule inhibitors of RIPK1 Kinase, also blocking necroptosis, would be an effective therapeutic option for patients with liver damages and HCC.…”
Section: Nf-κb and Necroptosis In Cancermentioning
confidence: 99%